2006
DOI: 10.1182/blood-2006-04-016949
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cardiac complications by deferiprone and deferoxamine combination therapy in a patient affected by a severe type of juvenile hemochromatosis (JH)

Abstract: Juvenile hemochromatosis (JH) is a rare autosomal recessive disorder of iron metabolism, genetically heterogeneous. In JH, symptomatic organ involvement occurs as early as the second decade of life. Heart failure and/or arrhythmias are the most frequent causes of death. Phlebotomy is the safest, most effective, and most economic therapeutic approach in hemochromatosis patients but is not indicated during the treatment of severe congestive heart failure with unstable hemodynamic status. The treatment of iron ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 16 publications
2
52
0
4
Order By: Relevance
“…The man-woman ratio for median serum ferritin levels for ages 18 -45 years is 3.8, which is similar to the increased risk for heart disease, with the reduced risk against heart disease in women ending with the onset of menopause. Epidemiologic studies in overt iron overload states such as transfusional iron overload and hemochromatosis have shown that the incidence of cardiac disease is increased (64) and that treatment with iron chelation improves cardiovascular outcome (27,86,87). Similarly, several studies have demonstrated a direct association between increased iron intake, body iron stores, and cardiovascular risk in the general population.…”
Section: The Role Of Iron In Endothelial and Vascular Diseasementioning
confidence: 99%
“…The man-woman ratio for median serum ferritin levels for ages 18 -45 years is 3.8, which is similar to the increased risk for heart disease, with the reduced risk against heart disease in women ending with the onset of menopause. Epidemiologic studies in overt iron overload states such as transfusional iron overload and hemochromatosis have shown that the incidence of cardiac disease is increased (64) and that treatment with iron chelation improves cardiovascular outcome (27,86,87). Similarly, several studies have demonstrated a direct association between increased iron intake, body iron stores, and cardiovascular risk in the general population.…”
Section: The Role Of Iron In Endothelial and Vascular Diseasementioning
confidence: 99%
“…A recent study by Fabio et al demonstrated that combined chelation therapy with deferoxamine and deferiprone successfully reversed the effects of heart failure in the setting of unrecognized juvenile hemochromatosis [6]. Therefore, iron chelation may prove useful in hemochromatosis cases where phlebotomy is not indicated or feasible.…”
Section: Systemic Iron Overload: Hemochromatosismentioning
confidence: 99%
“…We recommend the following management strategy: ·d −1 (the total dose given in 3 divided doses). 50,[221][222][223][224][225][226] 5. Supportive hemodynamic therapy should be geared to maintain cerebral and renal perfusion, avoiding aggressive inotropic therapy, which can be detrimental.…”
Section: Management Of Acute Decompensated Hf In Tmmentioning
confidence: 99%